(untitled) (Zoological Records and Reviews, 2025)
Zoological records and reviews – the systematic documentation, curation, and synthesis of knowledge about animal diversity, distribution, ecology, and conservation status – form the foundational knowledge infrastructure upon which all zoological research, biodiversity assessment, and wildlife management depend. Yet this infrastructure faces unprecedented challenges alongside extraordinary opportunities: the volume of primary zoological literature has grown to over 180,000 publications annually, exceeding human capacity for comprehensive synthesis; taxonomic records remain incomplete for the vast majority of described species; digital transformation has created both powerful new tools for literature mining, automated synthesis, and open data aggregation, and new risks of data quality degradation, predatory publishing, and reproducibility failure; and the demands of international biodiversity policy frameworks – Kunming-Montreal GBF, EU Nature Restoration Law, EU Biodiversity Strategy 2030 – for timely, comprehensive, and policy-relevant zoological evidence have never been greater. This review synthesises evidence from 168 primary studies (2010-2025) examining the challenges and opportunities in zoological recording, literature synthesis, open data provision, and knowledge translation for European and global biodiversity contexts. We evaluate five major challenge-opportunity domains: taxonomic knowledge gaps and digital taxonomy, literature synthesis at scale (systematic reviews and meta-analyses), open data infrastructure and FAIR principles, predatory publishing and research integrity, and knowledge translation to policy and practice. A forward-looking framework for transforming European zoological records and review practice in the 2025-2040 period is proposed, aligned with EU open science mandates and international biodiversity knowledge infrastructure investments.